1994
DOI: 10.1161/01.str.25.5.1010
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow reserve assessment in symptomatic versus asymptomatic high-grade internal carotid artery stenosis.

Abstract: Thromboembolic stroke is likely to occur in patients with a restricted cerebral blood flow reserve. Our aims were to determine (1) whether symptomatic patients had any significant hemodynamic restriction ipsilateral to carotid occlusive disease compared with patients whose carotid stenosis is asymptomatic and (2) whether patients with carotid occlusive disease have impaired cerebral perfusion reserve compared with control subjects. We compared cerebral blood flow and collateral capacity using the 133… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0
5

Year Published

1996
1996
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 27 publications
(12 reference statements)
2
15
0
5
Order By: Relevance
“…Although several studies showed impaired reserve capacity that improved after CEA in these patients, 12,18 other studies failed to show decreased reserve capacity 19 or showed impaired reactivity and subsequent improvement after CEA only in a small subgroup of patients. 17 Because we found no indication of vasodilatory compensation (no increased rCBV), we speculate that the beneficial effect of CEA in patients with a unilateral severe stenosis of the ICA is caused by removal of the embolic source rather than by restoration of the cerebral blood flow.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although several studies showed impaired reserve capacity that improved after CEA in these patients, 12,18 other studies failed to show decreased reserve capacity 19 or showed impaired reactivity and subsequent improvement after CEA only in a small subgroup of patients. 17 Because we found no indication of vasodilatory compensation (no increased rCBV), we speculate that the beneficial effect of CEA in patients with a unilateral severe stenosis of the ICA is caused by removal of the embolic source rather than by restoration of the cerebral blood flow.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies did not report significant hemodynamic changes after CEA 7,16,17,19 ; other studies did find significant changes. 8,12 Other studies report that significant hemodynamic changes after CEA may occur in some but not all patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 The degree of carotid stenosis correlates poorly with cerebral perfusion pressure, and several studies have been unable to detect any significant cerebral hemodynamic abnormality in a majority of patients with a high-grade CS. [2][3][4] Several other reports indicate the importance of cerebral hemodynamics in association with the risk of stroke in patients with CS or occlusion. [5][6][7][8] Carotid endarterectomy (CEA) improves the outcome of patients with symptomatic high-grade CS, 9 but its role in asymptomatic CS is less beneficial.…”
mentioning
confidence: 99%
“…[5][6][7] Many studies have been conducted to evaluate hemodynamic and/or metabolic status in these patients, but the results are conflicting. [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We used positron emission tomography (PET) to assess the regional cerebral hemodynamics and metabolism in patients with severe symptomatic ICA stenosis before and after CEA.…”
mentioning
confidence: 99%